Pangan Lokal, Ibu, Dan Stunting: Studi Kasus Praktik Pemberdayaan Gizi Keluarga Di Kupang - Bire Manoe, Lenny Sofia; Pellu, Susana Cecilia Lestyani; Ndandara, Aelsthri (Institut Agama Islam Negeri Ponorogo, 2025)
The adaptation of nutrition policies in East Nusa Tenggara (NTT) has so far been largely focused on technical aspects such as supplementary food distribution, fortification, and medical interventions, while paying little attention to the social and cultural practices that underpin nutritional resilience at the family level. This article explores how mothers in Kupang City have developed empowerment practices based on local food as a strategy to address stunting problems. The study employed a qualitative approach with a case study design, involving in-depth interviews with ten housewives, two posyandu (community health post) cadres, and field observations of local food processing practices. The results revealed that mothers in Kupang play not only the role of child caregivers but also serve as agents of social change in ensuring family nutrition through innovative menus based on local food ingredients such as jagung bose (corn porridge), moringa (kelor), and various tubers. These practices demonstrate the interconnection between local knowledge, gender roles, and efforts toward nutritional resilience—elements often overlooked in formal interventions. This study emphasizes that integrating local wisdom into nutrition policies can enhance the effectiveness of stunting reduction programs in food-insecure regions such as NTT.